The Effect of Industry Type, Company Size, Profitability, Leverage and Environmental Performance on Environmental Disclosure (Empirical Study on PROPER Participating Companies in 20182020) - Bramanda Maulana; Niswah Baroroh (Owner : Riset dan Jurnal Akuntansi, 2022)
Thei purpose of this study is to describe thei influence of industrial types, company size, profitability, leverage and environmental performance against Environmental Disclosure. The level of measurement of environmental disclosure is a chousier using GRI. There are 95 ratings scores in the detection of Disclosure environmental. The reference for this research is a study conducted by Burgwal and Vieirra (2014) conducted changes and improvements. The population in this study is a non financial company listed on the IDX in 2018 2020. The selected company for this study was 35 companies. The data collection used is purposive sampling, with the selection of Proper member companies. The data analyzed totaled 105 data. The main analysis of this study is multiple linear regression analysis. The results of the study show that industrial type variables, company size, profitability and environmental performance have a significant effect on environmental disclosure environment. While the leverage variable“does not significantly influence the environmental disclosure. Based on the regression results simultaneously obtained that 86.92% variations in industrial type variables, company size, profitability, leverage and environmental performance have a significant significantly influence on the environmental disclosure. Suggestions for companies should pay attention and improve the disclosure of environmental responsibilities. The government is also expected to consider environmental disclosure standards. And for further research it is necessary to develop other factors as an influence of environmental disclosure and use the measurement of other environmental disclosures.